2008
DOI: 10.1186/1471-2407-8-245
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer, psychological distress and life events among young women

Abstract: Since 1983, studies have suggested an interaction between the severe life events, psychological distress and the etiology of Cancer. However, these associations are still under dispute.The aim of the present study was to examine the relationship between life events, psychological distress and Breast Cancer (BC) among young women. Methods:A case control study. The study population included 622 women, under the age of 45 years. 255 were diagnosed for BC, and 367 were healthy women. A validated Brief Symptom Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 23 publications
3
52
1
9
Order By: Relevance
“…Finally, thirty (Aboudaoud, 1971;Henquin et al, 1994;Potashnik et al, 1999;Nustas et al, 2002;Alothaimeen et al, 2004;Gilani and Kamal, 2004;Yavari et al, 2005;Fakri et al, 2006;Lerner et al, 2006;Shaham et al, 2006;Faheem et al, 2007;Shema et al, 2007;Naieni et al, 2007;Mahouri et al, 2007;Katz et al, 2008;Peled et al, 2008;Montazeri et al, 2008;Saadat et al, 2008;Saleh et al, 2008;Ahmad et al, 2009;Calderon et al, 2009;Majid et al, 2009;Awatef et al, 2010;Abdulbari et al, 2010;Bidgoli et al, 2011;Ghiasvand et al, 2011;Hajian and Ahangar, 2011;Javed et al, 2011;Kloong et al, 2011;Tehranian et al, 2011) eligible studies included in the meta-analysis after quality assessment (Table 2 and Figure 1). Twenty five case-control studies, one nested case-control and four cohort studies were included.…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, thirty (Aboudaoud, 1971;Henquin et al, 1994;Potashnik et al, 1999;Nustas et al, 2002;Alothaimeen et al, 2004;Gilani and Kamal, 2004;Yavari et al, 2005;Fakri et al, 2006;Lerner et al, 2006;Shaham et al, 2006;Faheem et al, 2007;Shema et al, 2007;Naieni et al, 2007;Mahouri et al, 2007;Katz et al, 2008;Peled et al, 2008;Montazeri et al, 2008;Saadat et al, 2008;Saleh et al, 2008;Ahmad et al, 2009;Calderon et al, 2009;Majid et al, 2009;Awatef et al, 2010;Abdulbari et al, 2010;Bidgoli et al, 2011;Ghiasvand et al, 2011;Hajian and Ahangar, 2011;Javed et al, 2011;Kloong et al, 2011;Tehranian et al, 2011) eligible studies included in the meta-analysis after quality assessment (Table 2 and Figure 1). Twenty five case-control studies, one nested case-control and four cohort studies were included.…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, in a previous meta-analysis, Petticrew et al (1994) concluded that recent severe life events did not affect BC risk. In contrast, later cohort and casecontrol studies of the large sample size and estimation of the cumulative effect of life events which controlled the association for the confounding variables confirmed the positive association between cummulation of life events and BC development (Jacobs and Bovasso, 2000;Lillberg et al, 2003;Kruk and Aboul-Enein, 2004;Peled et al, 2008;Kruk, 2012). For example, Peled et al (2008) studied the relationship of a cumulative number of life events, psychological distress and BC risk.…”
Section: Psychological Stressmentioning
confidence: 93%
“…El estrés ocupacional puede causar consecuencias adversas para la salud (especialmente en períodos prolongados) como agotamiento, depresión, quejas psicosomáticas, deterioro de la salud (Morán, 2005a). En diferentes investigaciones hallamos que el estrés se encuentra relacionado negativamente con la satisfacción con la vida y la salud (Ciarrochi, Deane y Anderson, 2002;Morán, 2008;Peled, Carmil, Siboni-Samocha y Shoham-Vardi, 2008;Thompson et al, 2007).…”
Section: Introductionunclassified